Handling The Identification of Burn Victims in A Traffic Accident: A DVI Case Report - Novia, Hastin; Yudianto, Ahmad (Malaysian Journal of Medicine and Health Sciences, 2022)
The role of the forensic pathologist in a mass disaster is to identify the victims. The procedure refers to Interpol’s Disaster Victim Identification (DVI) guidelines. DVI consists of 4 stages namely Scene Examination, Post-Mortem Examination, Ante-Mortem Examination, and Reconciliation. Post-Mortem (PM) and Ante-Mortem (AM) data collected include fingerprints, dental records, DNA as Primary Identifiers, medical records, and property as Secondary Identifiers. At the reconciliation stage, at least there must be a match between one Primary Identifier or two Secondary Identifiers. Theoretically, 4-phase DVI should be performed according to the DVI standard in every disaster case. In fact, the implementation of DVI encountered many obstacles in the field. This article discusses the various obstacles and problems faced when conducting DVI in the case of a car accident with a truck on the Madiun-Ngawi toll road at KM 631 A to the Madiun – Nganjuk toll road. The chronology of this incident began when the elf’s vehicle hit a truck and a concrete barrier and then caught fire. Three victims were found in a burned condition leaving only the skeleton, thigh and psoas muscle. This of course does not allow fingerprints to be checked. The identification process is carried out only by comparing primary and secondary data as an identification guide given the condition of the bodies that are only slightly left. Then DNA examination was not carried out in this identification process. Tests for CO levels showed that the three victims indicated CO poisoning before they died.